The Use of Prophylactic Antibiotics for Cesarean Section Delivery and The Incident of Surgical Site Infection - Shofiatul Fajriyah; Umul Farida; Sri Agustina; Lelly Winduhani Astuti; Esti Ambar Widyaningrum (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
According to the 2018 Riskesdas data, the ratio of deliveries by cesarean section in 2018 was recorded at 17.6% of a total of 78,736 deliveries. One of the serious problems in postoperative treatment that has an impact on increasing morbidity, mortality, and increasing medical costs is surgical site infection (SSI). To reduce the risk of infection, efforts are made by giving prophylactic antibiotics followed by surgical procedures. The aim of this study was to determine the use of prophylactic antibiotics in cesarean section surgery and to determine the incidence of surgical site infection (SSI) in patients after Sectio Caesarea surgery in one of a private hospital in Kediri City. This study was an observational descriptive study with retrospective data collection through tracing of medical record data of patients who underwent Caesarean section surgery in 2021. The samples that entered the inclusion criteria were patients who received surgical prophylaxis with antibiotics and returned to the hospital for control after 1 week postoperatively. Samples that met the inclusion criteria were 89 patients. The sampling technique used purposive sampling. This study collected data on prophylactic antibiotics used and the incidence of SSI on days 1, 3 and (7-10) postoperatively. The results showed that the types of prophylactic antibiotics in patients undergoing sectio caesarea were ceftriaxone 2 g (99%) and cefotaxime 2 g (1%). Whereas there were 3 patients (3%) who had SSI on days 7-10 postoperatively.